2000
DOI: 10.1128/jvi.74.16.7496-7507.2000
|View full text |Cite
|
Sign up to set email alerts
|

Murine Model of Interstitial Cytomegalovirus Pneumonia in Syngeneic Bone Marrow Transplantation: Persistence of Protective Pulmonary CD8-T-Cell Infiltrates after Clearance of Acute Infection

Abstract: ؉ memory CD8 T cells were found to persist in lung tissue. One can thus operationally distinguish an early CMV-positive IP (phase 1) and a late CMV-negative IP (phase 2). According to the definition, phase 2 histopathology would not be diagnosed as a CMV-IP and could instead be misinterpreted as a CMV-induced immunopathology. We document here that phase 1 as well as phase 2 pulmonary CD8 T cells are capable of exerting effector functions and are effectual in protecting against productive infection. We propose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
149
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(160 citation statements)
references
References 47 publications
10
149
0
Order By: Relevance
“…However, it was plausible that the activated T cells accumulated in the lungs of MCMVinfected mice because of another purpose, for example, a physiological role. The experiments by Podlech et al (30) as well as our previous results (1,2) and the data presented in this study identified the powerful MCMV-amplified response potential of the pulmonary CD8 T cells. They demonstrated not only the persistence of CD8 T cells even after virus clearance, but also their antiviral effect.…”
Section: Discussionmentioning
confidence: 69%
“…However, it was plausible that the activated T cells accumulated in the lungs of MCMVinfected mice because of another purpose, for example, a physiological role. The experiments by Podlech et al (30) as well as our previous results (1,2) and the data presented in this study identified the powerful MCMV-amplified response potential of the pulmonary CD8 T cells. They demonstrated not only the persistence of CD8 T cells even after virus clearance, but also their antiviral effect.…”
Section: Discussionmentioning
confidence: 69%
“…Indeed, ample evidence from immunocompromised transplant or HIV patients documents a crucial role of the immune system, particularly CD8 + T cells, in anti-CMV immunity and in controlling the virus and CMV disease in these individuals (2). In murine models, IE-1-specific CD8 + T cells protected mice from a lethal challenge dose of virus, both in acute infection and following bone marrow transplantation with simultaneous murine CMV infection (28,29). The few available human studies comparing the protective capacity of pp65-or IE-1-specific immune responses tend to be contradictory.…”
Section: Discussionmentioning
confidence: 99%
“…An impact of vRAPs might rather be seen in the immunocompromised host, especially in the clinically relevant situation of lymphohematopoietic reconstitution of antiviral CD8 T cells in BMT recipients. Importantly, whereas CD8 T cells can be replaced with other innate and adaptive effector cells in otherwise immunocompetent mice (20), antiviral CD8 T cells are essential for preventing CMV disease in the BMT setting (30,31). Although deletion of vRAP m152/ gp40 can also activate NK cells through expression of the activating NKG2D ligand RAE-1 (for a review, see reference 24), previous work has demonstrated that CD8 T cells outperform NK cells in controlling the in vivo replication of mCMV⌬vRAP (4).…”
mentioning
confidence: 99%
“…Here we focused on infection of the lungs, since interstitial pneumonia is a very relevant manifestation of CMV disease in BMT recipients (39) and since the lungs are a major organ site of mCMV latency after neonatal infection (2) and after experimental BMT (22,30). Figure 1 sketches the experimental protocol of syngeneic BMT (Fig.…”
mentioning
confidence: 99%